Comparison between bulls and steers of the Brahman breed on growth, yield and meat quality in a system located in the North Pacific of Costa Rica - Salas-Elizondo, Juan Carlos (2020)
The present research evaluated the effect of sexual condition on the growth performance, carcass composition and beef quality of Brahman breed bullocks and steers in feedlot. Twenty-three animals were evaluated, these were randomly selected and divided in two treatments, T1: 11 bullocks and T2: 12 steer’s scrotal band castrated at birth. All animals were weaned at seven months of age and were finished in a feedlot at the age of 443 days. The study was conducted in three stages: the first one was carried out at San Julian beef cattle ranch in Guanacaste province, in the Pacific North of Costa Rica; the second one at the CIISA-Arreo packing plant, located in La Rivera, Belén, Heredia; and the third one was at the National Meat Laboratory, property of the Center for Research and Development in Sustainable Agriculture for Humid Tropic (CIDASTH). Average daily gain and growth (final farm weight) were statistically different and greater for T1, that might be associated with the effect of testosterone. Final packing plant weight, hot and cold carcass weight were statistically higher for T1, while the dressing percentage was greater and statistically different for T2. On the ribeye area (REA), T1 was greater and statistically different compared to T2. Fat thickness, carcass length, decrease of hot to cold carcass and muscular pH at 24 hours were no different among treatments. Shear force measured on the Longissimus dorsi at 14 days of wet aging, cooking loss and muscle color ((L, a *, b *) were no different among treatments; however, T1 had more purge loss than T2.